Long‐Term Safety and Efficacy of Epratuzumab in the Treatment of Moderate‐to‐ Severe Systemic Lupus Erythematosus: Results From an Open‐Label Extension Study. Issue 4 (24th March 2016) - Wallace, D. J.; Hobbs, K.; Clowse, M. E. B.; Petri, M.; Strand, V.; Pike, M.; Merrill, J. T.; Leszczyński, P.; Neuwelt, C. M.; Jeka, S.; Houssiau, F.; Keiserman, M.; et al.
Abstract : Objective: The primary objective was to assess the long‐term safety of repeated courses of epratuzumab therapy in patients with moderate‐to‐severe systemic lupus erythematosus. Secondary objectives were to assess long‐term efficacy and health‐related quality of life (HRQOL). Methods: Eligible patients from the 12‐week, phase IIb, randomized, placebo‐controlled EMBLEM study enrolled into the open‐label extension (OLE) study, SL0008. In the SL0008 study, patients received 1, 200 mg epratuzumab infusions at weeks 0 and 2 of repeating 12‐week cycles, plus standard of care. Safety measures included treatment‐emergent adverse events (TEAEs) and serious TEAEs. Efficacy measures included combined treatment response, the British Isles Lupus Assessment Group score, the Systemic Lupus Erythematosus Disease Activity Index score, and the physician's and patient's global assessment of disease activity. Total daily corticosteroid dose and HRQOL (by the Short Form 36 health survey) were also assessed. Results: A total of 113 of the 203 patients (55.7%) who entered the SL0008 study continued epratuzumab therapy until study closure (total cumulative exposure: 381.3 patient‐years, median exposure: 845 days, and maximum exposure: 1, 185 days/approximately 3.2 years). TEAEs were reported in 192 patients (94.6%); most common were infections and infestations (68.0%, 138 patients). Serious TEAEs were reported in 51 patients (25.1%), and 14 patients (6.9%) had serious infections. In patients treated for 108 weeks (n = 116), the median corticosteroid dose was reduced from 10.0 mg/day at OLE screening to 5.0 mg/day at week 108. Improvements in efficacy and HRQOL measures in EMBLEM were maintained in the OLE, while placebo patients exhibited similar improvements in disease activity upon a switch to epratuzumab. Conclusion: Open‐label epratuzumab treatment was well tolerated for up to 3.2 years, and associated with sustained improvements in disease activity and HRQOL, while steroids were reduced.